Investigation of the Effect of the COVID-19 Pandemic Period on Respiratory Tract Viruses at Istanbul Medical Faculty Hospital, Turkey - Sevim Mese; Aytaj Allahverdiyeva; Mustafa Onel; Hayriye Kırkoyun Uysal; Ali Agacfidan (Infectious Disease Reports, 2024)
Aim: Respiratory viruses significantly impact public health, contributing to high morbidity and mortality rates in both children and adults. This study evaluates the distribution and incidence of respiratory tract viruses in our hospital from 2019 to 2022, focusing on changes post-COVID-19 pandemic. Material and Methods: Utilizing molecular methods, we analyzed nasopharyngeal swabs with the FTD Respiratory Pathogens 21 kit and the QIAStat Dx Respiratory Panel kit at Istanbul Faculty of Medicine. A total of 1186 viruses were detected in 2488 samples (47.6% of the total) examined with the FTD Respiratory Pathogens 21 kit between 2019 and 2022. Results: It was determined that the detection rates were 52.8% in 2019, 44.3% in 2020, 50.0% in 2021, and 40.0% in 2022. Notable changes in prevalence were observed for pandemic influenza A (IAV-H1N1pdm2009), parainfluenza virus (PIV)-3, rhinovirus (RV), and respiratory syncytial virus (RSV)-A/B (p < 0.05). RV consistently showed the highest detection rates across all years (17.6% to 7.9%). Additionally, 1276 viruses were detected in 1496 samples using the QIAStat DX kit, with 91.3% positivity in 2021 and 78.6% in 2022, highlighting the kit’s effectiveness in rapid diagnosis. Conclusions: This study enhances understanding of respiratory virus epidemiology during and after the pandemic, emphasizing the need for ongoing surveillance and strategic public health measures to address the evolving landscape of respiratory infections.